Photodegradation Of Methyl Orange (MO) Using TiO2/Zeolite From Coal Fly Ash Waste Under Acidic Conditions and H2O2 Addition - Prakoso, Muhamad Iqbal; Maharani, Khairy Yunda; Ariq, Muhammad Rizki; Indah, Amalia Nurul; Apriansyah, Apriansyah; Iryani, Ani; Kusumawardani, Linda Jati; Syahputri, Yulian (Universitas Pakuan, 2024)
This study aims to degrade methyl orange dye by a photocatalytic method using TiO2/zeolite nanocomposite. The zeolite used is sourced from coal waste fly ash. While the TiO2/Zeolite nanocomposites were synthesized by the sol-gel method and analyzed using UV-Vis DRS to determine the band gap energy. The band gap energy obtained from calculation results of the Kubelka-Munk formula shows a value of 2.0 eV. This indicates that the working area of methyl orange photodegradation using TiO2/zeolite is in visible light. Optimization of the methyl orange photodegradation process in this study will be carried out in an acidic environment by varying the nanocomposite dose (0.05; 0.1; 0.2; 0.3; and 0.4 g) and the length of time of irradiation (15; 30; 45; 60; and 75 minutes). This study also conducted a study on the effect of adding H2O2. The optimum yield of percent degradation (%D) of methyl orange (MO) obtained was 98.37% from initial concentration 10 mg/L to 0,16 mg/L with varying doses of TiO2/zeolite 0.1 g and 30 minutes in an acidic environment and the addition of H2O2.